Analisis Nilai-nilai Pendidikan Islam dalam Cerita Animasi Ubay - Zahrawani, Sintya Nur; Wardefi, Riza (TSAQOFAH, 2025)
This study aims to analyze Islamic educational values, particularly the concept of tawhid (oneness of God), in the animated series Ubay produced by Yufid TV as an alternative learning medium for children in the digital era. Islamic values need to be instilled from an early age to enable younger generations to fully understand and practice Islamic teachings, while exposure to digital content that does not align with Islamic principles presents a significant challenge. Using a qualitative approach and content analysis method, this study explores how tawhid values are conveyed in each episode of the Ubay animation. The findings show that the animation successfully delivers tawhid teachings through narratives emphasizing the recognition of God's oneness, the importance of prayer, gratitude, patience, empathy, and understanding Allah as the Creator. These values are communicated through storytelling, dialogue, and habituation methods presented in a simple and interactive manner, making it easier for children to comprehend and internalize the moral messages conveyed. The findings affirm that Ubay serves not only as entertainment but also as an effective educational medium for contextualizing Islamic values. The implication is that digital media products integrating religious messages such as Ubay can serve as valuable references in developing Islamic value-based learning media for early childhood education.